Self-aligned hybrid carrier-based PWM for modular multilevel converters - Le Nam Pham; Quoc Dung Phan (Institute of Advanced Engineering and Science, 2023)
The self-aligned hybrid carrier-based pulse-width modulation (PWM) for modular multilevel converters (MMC) based on decentralized control is proposed in this paper. It is based on parallel cells in a submodule (SM) using self-aligned hybrid carrier-based PWM, which combines the concept of level-shifted carrier-based PWM (LSC-PWM) and phase-shifted carrier-based PWM (PSC-PWM) methods. By implementing a decentralized control system digitally, hybrid carriers align themselves. Each SM interacts with the other SMs and each parallel cell in an SM communicates with the other cells to generate hybrid carriers. The proposed control strategy makes advantage of the redundancy idea by adding or removing a cell in the case of cell malfunction and system reconfiguration. A current balancing method is incorporated into the decentralized control system to ensure current balance among parallel cells in an SM. The simulation results illustrate the effectiveness of the presented control method in piecewise linear electrical circuit simulation (PLECS) software.